Discretionary Accounting Choices and CEO Compensation* - BALSAM, STEVEN (Contemporary Accounting Research, 1998)
This paper makes four contributions to the literature relating accounting choices to CEO compensation. First, it shows that discretionary accruals are associated with CEO cash compensation, a result that holds after controlling for both the nondiscretionary components of income and increases in shareholder wealth. Although significant, the coefficient on discretionary accruals is significantly lower than that on nondiscretionary accruals, which in turn is significantly lower than the coefficient on operating cash flows. Second, the paper shows a differential reaction to positive and negative discretionary accruals —‐ the association between positive discretionary accruals and CEO cash compensation is significantly greater than the association between negative discretionary accruals and CEO cash compensation. Third, the paper shows the association between discretionary accruals and CEO cash compensation varies depending upon the circumstances of the firm. In particular, when positive discretionary accruals allow the firm to reduce or avoid a loss, the association between CEO cash compensation and discretionary accruals is significantly greater. Finally, this paper shows that the association of CEO cash compensation with reported income generally increases with the level of discretionary accruals, consistent with management responding to the incentives provided.